2011
DOI: 10.1061/(asce)cp.1943-5487.0000082
|View full text |Cite
|
Sign up to set email alerts
|

Military Facility Cost Estimation System Using Case-Based Reasoning in Korea

Abstract: Numerous cost estimations are made repetitively in the initial stages of construction projects in response to ongoing scope changes and often need to be recalculated frequently. In practice, the square foot method, considered an effective method for time-saving, is widely used. However, this method requires a great amount of effort to calculate a unit price and does not consider the uniqueness of each case. Thus, the use of the square foot method could bring about unwanted consequences. For example, in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In this study, CBR was applied to estimate the repair times of building components. CBR is an artificial intelligence method based on the work of cognitive scientists Schank and Abelson [24] that solves problems [1,25] based on data and knowledge obtained from past similar cases [1]. It has been applied to various fields, such as construction cost estimation, bid mark-up estimation, construction noise prediction, construction hazard identification, and building maintenance [1,[26][27][28][29].…”
Section: Case-based Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CBR was applied to estimate the repair times of building components. CBR is an artificial intelligence method based on the work of cognitive scientists Schank and Abelson [24] that solves problems [1,25] based on data and knowledge obtained from past similar cases [1]. It has been applied to various fields, such as construction cost estimation, bid mark-up estimation, construction noise prediction, construction hazard identification, and building maintenance [1,[26][27][28][29].…”
Section: Case-based Reasoningmentioning
confidence: 99%
“…Finally, the revised results are retained in the database as a new case [31]. This study focused on phases of retrieving and reusing because they are important phases of CBR [24,31]. The revising and retaining phases will be addressed in future studies.…”
Section: Case-based Reasoningmentioning
confidence: 99%
“…Koo et al [15,16] developed a CBR-based hybrid model for predicting the duration and cost of a construction project. Ji et al [4,17,18] developed a CBR cost model and suggested a CBR cost estimation system for public projects.…”
Section: Cost Models In Constructionmentioning
confidence: 99%
“…It is important to note that cost estimation is a knowledge-intensive engineering work and requires expertise of the human professionals [18,20]. However, there are difficulties in utilizing engineers' expertise since experienced knowledge is not often documented and this eventually leads to subjectivity [18]. erefore, further research is required to compensate subjectivity of experts and support decision-making regarding cost estimation of plausible alternatives in a quantitative manner.…”
Section: Cost Models In Constructionmentioning
confidence: 99%
“…Doğan (2008) proposed another data mining technique that is called the decision tree model. Ji and Kim (2011) proposed a cost prediction algorithm that combines CBR and GA. Park et al (2011) proposed a quantity prediction method for the design development stages that uses the standard database for quantities of reinforcing bars. This method allows users to directly connect to case-based data and perform cost estimations, since reinforcing bar objects are not employed in the design development stages.…”
Section: Literature Reviewmentioning
confidence: 99%